Apparent survival rates of a long-lived partial migrant: the Yellow-legged Gull Larus michahellis. Issue 2 (3rd April 2018) - Kralj, Jelena; Jurinović, Luka; Barišić, Sanja; Ćiković, Davor; Tutiš, Vesna
ABSTRACT: Capsule: In Yellow-legged Gull Larus michahellis populations from the eastern Adriatic Sea, there are considerable differences in the ratio of migratory birds and apparent survival among the colonies. Survival was dependent on age, colony and area of dispersal. Aims: To identify the ratio of migratory birds within populations of Yellow-legged Gulls, and to compare apparent survival of gulls during migration in central and northern Europe and around the Adriatic Sea. Methods: We analysed 15 years of resighting data of Yellow-legged Gulls using a MARK multi-state model to calculate survival rates. The effects of age, natal colony and area of dispersal were examined. Results: Almost 60% of Adriatic Yellow-legged Gulls were migratory but the ratio varied among colonies (10.3–78.3%). Survival was dependent on age, colony and area of dispersal, with average values per group ranging between 0.599 (se 0.093) and 0.684 (se 0.084). Conclusion: The ratio of migratory and dispersive Yellow-legged Gulls from different Adriatic colonies might be affected by both inheritance and food availability.